THE INFLUENCE OF THE LANGUAGE ENVIRONMENT ON THE ARABIC SPEAKING SKILLS OF CLASS VIII STUDENTS AT MADRASAH TSANAWIYAH AL-ITTIFAQIAH INDRALAYA: PENGARUH LINGKUNGAN BERBAHASA TERHADAP KETERAMPILAN BERBICARA BAHASA ARAB SANTRI KELAS VIII DI MADRASAH TSANAWIYAH AL-ITTIFAQIAH INDRALAYA - lulu ilmaknun (Program Studi Pendidikan Bahasa Arab Fakultas Tarbiyah IAI Al-Qur'an Al-Ittifaqiah Indralaya, 2024)
This research aims to investigate both the presence and the degree of influence that the language environment has on Arabic speaking skills, as well as the strength of the relationship between these two factors. Employing a quantitative methodology with a correlational approach, the study utilizes the Pearson product-moment correlation test for data analysis, facilitated by the SPSS version 19 software. The sample population consists of 55 students from class VIII at Pondok Pesantren Al-Ittifaqiah Putri. The findings indicate a significance value of 0. 035.